PELAKSANAAN DISIPLIN PEGAWAI BERDASARKAN PERATURAN PEMERINTAH PEMERINTAH NOMOR 53 TAHUN 2010 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL PADA KEJAKSAAN TINGGI KALIMANTAN TIMUR (Studi Kantor Kejaksaan Tinggi Kalimantan Timur) - Damayanti Damayanti; Hudali Mukti (Yuriska: Jurnal Ilmiah Hukum, 2016)
As has been mandated in legislation, the state apparatus in improving the quality of Administrative by improving welfare and professionalism as well as enacting system careers based on performance with the principle of reward and punishment, the State Apparatus should be able to be disciplined in achieving good governance and authoritative. Administrative Reform continues to be improved, especially with regard to quality, service efficiency, and protection of the public as well as professional skills, and well-being are all concerned agencies in supporting the implementation of tasks. In fact still many state officials who commit violations in the form of sanctions Weight Environmental example that occurred in the high Court as Satya Adhi Wicaksana. In order To create clean governance and authoritative, certainly needed discipline of the officials and personnel administration. Therefore we need a set of rules that can support the creation of employee discipline.